Pemanfaatan Fitur Bot Telegram Sebagai Pengendali Pada Sistem Penyiraman dan Pemupukan Bibit Kelapa Sawit - Darusman, Landra Rizky; Sulaiman (Universitas PGRI Palembang, 2023)
The Indonesian oil palm plantation industry as the largest producer plays a vital role in the economy. Seed quality is the focus to meet increasing market demand. Watering and fertilizing the oil palm seedlings plays an important role in cultivation. Messaging application-based automation solutions such as Telegram promise convenience. By leveraging the Telegram bot feature, this tool can be operated remotely, providing effective control over watering and fertilizing. Benefits include time efficiency, proper fertilization, andaccurate watering for quality seeds. Light sensors and soil moisture help optimize the process, this tool proved successful in trials. Thus, this automated solution has the potential to increase productivity and efficiency in oil palm cultivation, addressing the problem of irregular watering and fertilizing.